Strategi Dakwah Nahdlatul Ulama dalam Membentengi Nahdliyin Dari Radikalisme di Kota Subulussalam - Baharudin Pasaribu; Soiman Soiman (Dinasti Research, 2024)
This research aims to identify Nahdatul Ulama's effective da'wah strategy in protecting Nahdliyin from Radicalism in the city of Subulussalam and evaluate the factors that influence the successful implementation of this strategy. The research method used is field research with a qualitative approach which aims to analyze Nahdlatul Ulama's da'wah strategy in protecting Nahdliyin from radicalism in the city of Subulussalam and includes interviews and observations in order to gain an in-depth understanding of the efforts made by Nahdlatul Ulama in fighting against it. radicalism among the Nahdliyyin. The results of this research show that Nahdlatul Ulama in Subulussalam City has succeeded in implementing an effective da'wah strategy in fighting radicalism. By delivering da'wah material that involves the values ​​of tolerance, balanced education, critical thinking, inter-religious dialogue, social justice, moderation and empathy as an effort to prevent radicalism.